Temporal Electret Behavior of Polymer Films Exposed to Cold Radiofrequency Plasma. Issue 8 (3rd January 2015) - Bormashenko, Edward; Pogreb, Roman; Chaniel, Gilad; Multanen, Victor; Malkin, Alexander Ya.
<x xml:space="preserve">Abstract</x> The paper examines the electret response of cold plasma treated polypropylene and low‐density polyethylene films. Films were loaded with oscillating mechanical load; the output voltage was registered by a lock‐in amplifier. In parallel, hydrophobic recovery of the films was studied by the measurement of the apparent water contact angle. Time dependencies of electret response and hydrophobic recovery demonstrated qualitatively very similar behavior. Three distinct scale times of electric and hydrophobic restoring were extracted from the time dependencies of electric decay and hydrophobic recovery, extending from minutes to hundreds of minutes.